Evaluation of diabetic wound healing properties of moringa oleifera lam using in vitro and in vivo wound models - Muhammad Amali, Abubakar (2015)
Diabetic wound is a common complication which affects significant number of people with diabetes. Its treatment is often very difficult which imposes burden and high cost on patients,family and society. Current treatments of diabetic wound are not sufficient enough with limited success in addition to non-affordability. Moringa oleifera Lam (M. oleifera) from the family Moringaceae (genus Moringa) commonly called drumstick or horseradish is a plant traditionally employed in the treatment of many ailments and has been scientifically proven to possess hepatoprotective, anti-inflammatory, antioxidant and hypoglycemic action in addition to other numerous activities. The present study was undertaken to evaluate the potential of M. oleifera on wound healing in diabetic condition with a view to providing possible cost effective therapeutic alternative for treating diabetic wound topically. In vitro and in vivo wound models were utilized for our study. The study initially demonstrated screening of crude extracts of methanol, ethanol and aqueous from Moringa oleifera leaves. Among these three solvent crude extracts, the methanolic crude extract was found to be the most active crude extract following the in vitro screening. The most active methanolic extract was then further subjected to bio-assay guided fractionation using hexane, dichloromethane, ethyl acetate, butanol and aqueous. The aqueous fraction was proven to be the most active fraction obtained from the results of in vitro screening and bio-guided assay fractionation. The in vitro study included scratch test and proliferation assays using human dermal fibroblast cells (HDF), in which three different solvent crude extracts were screened and the most active methanolic crude extract was further subjected to differential bio graded assay fractionation. The most active aqueous fraction was finally obtained. HPLC, LC-MS/MS and UV spectroscopy were used for the identification and confirmation of bioactive compounds. Kaempferol and quercetin were identified in the crude methanolic extract while an active compound vicenin-2 was identified, confirmed and quantified in the bioactive aqueous fraction. Antioxidant and antibacterial assays were also conducted. The in vivo study involved topical application of the formulated bioactive fraction using full thickness excision wound model in streptozotocin (STZ) and nicotinamide (NAD) induced diabetic rats. Healthy adult male Wistar rats weighing between 150-250g were used. Animals were grouped into six, consisting of six rats in each group (n=6): Two groups of normal and diabetic controls, three groups of 0.5%, 1% and 2% w/w, aqueous fraction treated and one group of positive control that received 1% w/w silver sulfadiazine as standard drug. Treatments were applied topically in form of cream to the skin wounded area for 21 days. Biophysical, biochemical and histological parameters were evaluated. Proinflammatory cytokines analyses were performed using ELISA, Western blotting and immunohistochemistry techniques. Results were analyzed using SPSS version 20. Data were expressed as mean ± standard deviation, and results were selected from at least three independent experiments performed in triplicate. P-values of 0.05 were considered to be statistically significant. The in vitro test results demonstrated that, crude methanolic extract and aqueous fraction of M. oleifera significantly stimulated proliferation and migration of HDF cells (p<0.05) at 24,48 and 72 hours after treatment to close the artificially wounded area when compared to untreated control cells. The distance was measured and analyzed quantitatively at time interval of 0, 24, 48 and 72 hrs after the scratch. The MTT assay results showed that,aqueous fraction was relatively non-toxic and did not affect the cellular activity of HDF cells even at concentrations of 800 μg/mL after 72 hours. The aqueous fraction was tested and found to be effective in enhancing wound healing in vitro through proliferation and migration of human dermal fibroblast cells. In addition, antioxidant and antibacterial activities demonstrated by the bioactive aqueous fraction through radical scavenging and ferric reducing abilities as well inhibition of growth of S. aureus, Ps. aeruginosa and E. coli bacterial pathogens. Following induction of diabetes by STZ-NAD in Wistar rats, hyperglycemia was maintained for 21 days and the reading of blood glucose level was more significant in diabetic groups compared to normal control group (p < 0.05). There was also some form of partial destruction of Islet of Langerhans and some normal islets were seen to be preserved even after the administration of a low dose of STZ and NAD which mimics the type-2 diabetes seen in humans. The in vivo topical applications of various doses (0.5%, 1% and 2%) of bioactive aqueous fractions was found to be effective in enhancing diabetic wound healing through overall decreased wound size, improved wound contraction, enhanced tissue regeneration and granulation tissue, the decrease wound size in diabetic treated groups was more significant compared to untreated diabetic control group (P < 0.05) and there was also significant difference in contraction rate between diabetic treated groups compared to untreated diabetic control group (P < 0.05). The topical application of aqueous fraction to the wound of diabetic animals caused down regulation of inflammatory mediators (TNF-α, IL1-β, IL-6, iNOS and COX-2) that was very significant in the diabetic treated groups as compared to non-treated diabetic control animals (p<0.05). The up regulation of VEGF protein in the diabetic treated groups was also found to be more significant (P < 0.05) compared to untreated diabetic control group that had less expression of VEGF. Down regulation of inflammatory mediators and up regulation of VEGF with M. oleifera aqueous fraction facilitates overall wound healing and closure in diabetic condition. The bioactive compounds present in aqueous fraction have also been successfully identified and confirmed by HPLC and LC-MS/MS using standard vicenin-2 compound. These findings suggested that, topical administration of bioactive aqueous fraction of M. oleifera containing Vicenin-2 compound may accelerate wound healing in hyperglycemic condition. Therefore, may serve as a lead in drug discovery for diabetic wound healing.